Teacher Identity and Agency Development of an Indonesian Islamic Junior High School: Bourdieu’s Lens - Ma’mun, Nadiah; Hartono, Rudi; Mujiyanto, Januarius; Pratama, Hendi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The construction of professional identity among English teachers in private Islamic junior high schools in Indonesia is a multifaceted process influenced by cultural, religious, and institutional factors. Utilizing Bourdieu’s Social Practice theory, which encompasses the concepts of habitus, capital, and field, this study aims to explore how these elements shape teacher agency and professional identity in this unique educational context. Through a qualitative research approach, involving in-depth interviews, data were collected from an English teacher at a private Islamic Junior high school. The participant was selected from among English teachers to represent them at an Islamic private school. The participant is considered to have qualified as a professional English teacher. He has participated in the in-service teacher certification program and has passed, receiving certification benefits. The findings reveal that teachers’ professional identities are shaped not only by their pedagogical skills and knowledge (capital) but also by their alignment with the religious and cultural values of the Islamic school environment (habitus). This alignment influences his sense of agency, affecting how he navigates his roles within the institutional structure (field). This research is particularly valuable for educators, school administrators, and policymakers involved in teacher education and professional development. It suggests that teacher education programs should incorporate strategies that address the cultural context of Islamic education while promoting teacher agency, ultimately benefiting those seeking to enhance the quality and effectiveness of English language teaching in similar educational settings.